2014
DOI: 10.1111/jcpe.12206
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue wound healing around teeth and dental implants

Abstract: Aim To provide an overview on the biology and soft tissue wound healing around teeth and dental implants. Material and Methods This narrative review focuses on cell biology and histology of soft tissue wounds around natural teeth and dental implants. Results and conclusions The available data indicate that: Oral wounds follow a similar pattern. The tissue specificities of the gingival, alveolar and palatal mucosa appear to be innately and not necessarily functionally determined. The granulation tissue origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
288
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(309 citation statements)
references
References 213 publications
(194 reference statements)
11
288
0
10
Order By: Relevance
“…The reduction in tissue changes observed within three month indicated achievement of tissue stability around implant. The results of this study support the efficacy of this procedure in maintaining the gingival architecture in accordance with similar studies [14,17,18]. In this study intra-oral periapical radiographs used for the assessment of bone level were obtained by using paralleling technique to minimize distortion and standardized by using occlusal putty jig.…”
Section: Discussionsupporting
confidence: 89%
“…The reduction in tissue changes observed within three month indicated achievement of tissue stability around implant. The results of this study support the efficacy of this procedure in maintaining the gingival architecture in accordance with similar studies [14,17,18]. In this study intra-oral periapical radiographs used for the assessment of bone level were obtained by using paralleling technique to minimize distortion and standardized by using occlusal putty jig.…”
Section: Discussionsupporting
confidence: 89%
“…2011c, Sculean et al. 2014). In fact, animal studies have shown that implant sites with narrower mucosal thickness consistently reveal marginal bone resorption to adjust for the acceptable biological width around implants (Berglundh & Lindhe 1996), which could be the clinical situation associated to PM when compared to PS restorations.…”
Section: Discussionmentioning
confidence: 99%
“…41 In this study, to figure out the roles of surface morphology during the soft tissue integration, both HGECs and HGFs from human gingival tissue were cultured on different titanium surfaces for systemic analysis. The data showed that after 24 hours of incubation, HGECs on the Nano surface spread readily and exhibited upregulated gene expression of integrin α6β4, the major component of the hemidesmosome, and laminin α3β3γ2 (laminin-5), the major component of the basement membrane, compared to the Smooth and Micro surfaces.…”
mentioning
confidence: 99%